An Overview of Processed Fruits Export from India: Growth, Status and Trend - Keerthika, B.; Thilagavathi, M.; Rani, C. Indu; Pragadeeswaran, M.; Vasanthi, R. (International Journal of Economic Plants, 2024)
The current study was conducted during 2022–23 and the data was collected for twenty years from 2001–02 to 2020–21 from different sources. India is the leading producer of Fruits as well as vegetables after China, producing about 99.07 million mt of fruits and 191.77 million mt of vegetables. Even though we are the largest producer,the wastage of horticultural commodities is very large due to improper post-harvest management and lack of awareness about storage.The commodity specific processing, preservation and value-addition should be used to reduce the wastage which will also increase the income of the farmers by exporting them to different countries. This study is proposed to analyse the commodity specific export in the processed fruits exports from India. The major products of processed fruits exports identified are jam, jelly and marmalades, mango pulp, dried fruits, juices, squash and preserved berries. The Compound annual growth rates were calculated and it was found that jam, jelly and marmalades had higher growth rate of 17% in terms of volume of export and dried fruits exports showed higher growth rate in terms of value with CAGR of 10.31%. Hence, scientific methods of value-addition and packaging facilities should be developed in the country to compete with the global processing industries which will increase the export to many countries.